Functional nanocomposite particles and preparation method thereof and application in virus detection
By preparing nanoferrous tetraoxide microspheres and coating yttrium-doped nanosilicon oxide shells, combining with reducing graphene oxide dispersion liquid to form multi-dimensional nanocomposite particles, the problem of insufficient dispersion and sensitivity of nanomaterials in the prior art is solved, and efficient virus detection is achieved.
Patent Information
- Application Number
- CN202110352937.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-04-01
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2041-04-01
AI Technical Summary
In the prior art, the nanomaterials used for virus detection are mostly three-dimensional nanospheres, and the multi-dimensional nanomaterial application of two-dimensional sheets and three-dimensional materials is lacking, resulting in insufficient detection sensitivity and dispersion.
By preparing nanoferrous tetraoxide microspheres with good dispersion, and covering their surface with yttrium-doped nanosilicon oxide shells, combined with reducing graphene oxide dispersion, multi-dimensional nanocomposite particles are formed by ultrasonic treatment to improve their specific surface area and dispersion.
The uniform dispersion and high stability of nanocomposite particles are achieved, the sensitivity and detection range of virus detection are improved, and multifunctional nanoprobes are suitable for virus detection.
Abstract
Description
Technical Field
[0001] The invention relates to the field of biotechnology, and in particular to a functional nano composite particle and a preparation method thereof, as well as application in virus detection. Background Art
[0002] Infectious diseases have seriously affected the development and progress of human health. The detection, prevention and treatment of infectious diseases are difficult problems in the medical field. Although the detection of viruses can effectively block the spread of infectious diseases, there is still a lack of efficient and rapid methods. In addition, the current control of viral infectious diseases is mainly based on vaccine prevention, but there is no effective treatment strategy for established viral infections. Inorganic nanomaterials have gained widespread attention in research fields such as virus detection due to their unique optical, thermal and electrical properties.
[0003] A notable feature of nanomaterials that are widely used in the biomedical field is that they are easy to modify and can be used as a platform for assembling multifunctional materials. After the nanoparticles are stably present, they can be easily functionalized with different molecules to provide more applications. Patent CN201110080438.1 discloses nanoparticles with lutetium fluoride as the main component for biological detection. The invention uses lutetium fluoride nanoparticles doped with rare earth elements, which have good conversion luminescence properties, can well achieve cell labeling, and have high detection sensitivity. Patent CN202010990209.2 discloses a preparation method, magnetic microspheres and applications of functionalized magnetic microspheres. The invention first prepares magnetic seed balls, and performs surface hydrophilic modification on the magnetic seed balls to obtain hydrophilic magnetic particles; and performs surface functionalization modification on the hydrophilic magnetic particles to obtain functionalized magnetic microspheres; wherein the surface functionalization modification includes silanol modification and sulfonic acid modification, and the above-mentioned magnetic seed balls can be used in virus detection. It can be seen from the above-mentioned prior art that the nanomaterials currently used for virus detection are mostly three-dimensional nanospheres, and research using multi-dimensional nanomaterials that use two-dimensional sheets and three-dimensional materials for virus detection is rare. Summary of the invention
[0004] The technical problem to be solved by the present invention is: in view of the shortcomings of the prior art, a functional nano composite particle and a preparation method thereof are provided. The present invention first prepares nano ferroferric oxide microspheres with good dispersibility, then coats the surface of the nano silicon oxide shell layer doped with yttrium to obtain nano composite particles, and finally mixes the nano composite particles with a reduced graphene oxide dispersion, ultrasonically treats the nano composite particles, and uniformly disperses the nano composite particles between the graphene oxide sheets and on the surface, thereby forming a multi-dimensional nano material with a large specific surface area, good dispersibility, and easier functional modification, and high sensitivity when used for virus detection.
[0005] In order to solve the above technical problems, the technical solution of the present invention is:
[0006] A functional nano composite particle comprises a graphene oxide substrate and nano composite particles dispersed between graphene oxide layers and on the surface; the nano composite particles comprise nano ferroferric oxide microspheres and a yttrium-doped nano silicon oxide shell layer coated on the outer layer of the nano ferroferric oxide microspheres.
[0007] The present invention also discloses a method for preparing functional nanocomposite particles, comprising the following steps:
[0008] (1) adding an iron source to deionized water to prepare an iron salt solution, slowly dropping an ammonia solution after heating for the first time, vigorously stirring and reacting for a period of time after the dropping is completed, then heating for the second time, aging treatment, and finally cooling to room temperature, centrifuging, washing the precipitate with deionized water and anhydrous ethanol in turn until neutral, drying and dispersing in anhydrous ethanol to prepare a nano-iron oxide microsphere dispersion;
[0009] (2) mixing tetraethyl orthosilicate and anhydrous ethanol to obtain a tetraethyl orthosilicate solution, then mixing the tetraethyl orthosilicate solution with a nano-iron oxide microsphere dispersion, ultrasonically treating the solution, then dropping an ammonia solution, performing a first stirring reaction, and finally dropping an yttrium nitrate solution, performing a second stirring reaction, and after the reaction is completed, centrifuging the reaction solution, washing the precipitate obtained by centrifugation until it is neutral, drying it, and finally calcining it to obtain nanocomposite particles;
[0010] (3) The nanocomposite particles prepared above are dispersed in deionized water, and then an ethanol dispersion of reduced graphene oxide is added, and ultrasonic treatment is performed at room temperature and a power of 300-500 W for 1-3 h, and then the precipitate is filtered and dried to obtain functional nanocomposite particles.
[0011] As a preferred embodiment of the above technical solution, in step (1), the iron source is a mixture of ferric chloride hexahydrate and ferrous sulfate heptahydrate, the molar ratio of the two is 2:1, the concentration of trivalent iron ions in the iron salt solution is 1-2 mol / L; the concentration of the ammonia solution is 20wt%, the dripping speed of the ammonia solution is 1.15-1.35ml / min, and the material ratio of ferric chloride hexahydrate to ammonia solution is 0.005mol:(2-3)ml.
[0012] As a preferred embodiment of the above technical solution, in step (1), the heating rate during the first heating is 5°C / min, the stirring speed of the stirring reaction is 3000-5000r / min, the time is 20-30min, and the temperature is 60-70°C; the heating rate during the second heating is 10°C / min, the temperature of the aging treatment is 80-85°C, and the time is 20-40min.
[0013] As a preferred embodiment of the above technical solution, in step (2), the concentration of the tetraethyl orthosilicate solution is 0.3-0.5 mol / L, the concentration of the nano-ferroferric oxide microsphere dispersion is 1-2 g / L, and the volume ratio of the tetraethyl orthosilicate solution to the nano-ferroferric oxide microsphere dispersion is 1:(1-2).
[0014] As a preferred embodiment of the above technical solution, in step (2), the concentration of the ammonia solution is 5-10wt%, the dripping speed of the ammonia solution is 0.35-0.55ml / L, the concentration of the yttrium nitrate solution is 0.08-0.12mol / L, and the dripping speed of the yttrium nitrate solution is 0.35ml / min; the volume ratio of the ammonia solution, the yttrium nitrate solution, and the tetraethyl orthosilicate solution is 1:(3-5):(60-70).
[0015] As a preferred embodiment of the above technical solution, in step (2), the stirring speed of the first stirring reaction is 5000-6000 r / min, the reaction time is 1-2 h, and the reaction temperature is room temperature; the speed of the second stirring reaction is 2000-3000 r / min, the reaction time is 4-6 h, and the reaction temperature is room temperature.
[0016] As a preferred embodiment of the above technical solution, in step (2), the calcination temperature is 400° C. and the calcination time is 2-3 hours.
[0017] As a preferred embodiment of the above technical solution, in step (3), the concentration of the ethanol dispersion of reduced graphene oxide is 0.1-0.2 g / L, and the material ratio of the nanocomposite particles, deionized water, and the ethanol dispersion of reduced graphene oxide is 0.5 g:100 ml:(100-200) ml.
[0018] As a preferred embodiment of the above technical solution, the functional nanocomposite particles prepared by the present invention can be applied to virus detection.
[0019] Due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0020] The present invention provides a functional nanocomposite particle, the nanomaterial comprises a reduced graphene oxide substrate, and nanocomposite particles dispersed between and on the reduced graphene oxide layers; the reduced graphene oxide has high mechanical strength, large specific surface area, and is easier to modify on the surface, and has good dispersibility; the nanocomposite particles comprise nano-iron tetroxide microspheres, and yttrium-doped nano-silicon oxide shells coated on the outer layers of the nano-iron tetroxide microspheres. The ferroferric oxide has good biocompatibility, but its dispersibility is poor. The present invention in-situ coats a layer of yttrium-doped nano-silicon oxide shells on the surface thereof, which not only improves the dispersibility of the nano-iron tetroxide microspheres, but also improves the stability of the nanoparticles, and the doping of yttrium improves the luminescent properties of the nanomaterial, and when it is used as a nanoprobe for virus detection, it has high sensitivity and a wide detection range.
[0021] The present invention uses ferric chloride hexahydrate and ferrous sulfate heptahydrate as iron sources, and ammonia solution as a precipitant, and controls the precipitation rate of the iron source by controlling the dripping speed of the ammonia solution, thereby preparing nano-iron tetroxide microspheres with good dispersibility; then, ethyl orthosilicate is used as a silicon source, and yttrium nitrate is used as a yttrium source, and a layer of yttrium nano-silicon oxide shell is coated on the surface of the nano-iron tetroxide microspheres, and the uniform dispersion and good coating of yttrium nano-silicon oxide on the surface of the nano-iron tetroxide microspheres are effectively improved by adjusting the dripping speed of ammonia solution and a staged reaction method. Finally, the prepared nano-composite particles are mixed with a reduced graphene oxide dispersion and ultrasonically treated. Under ultrasonic conditions, the sheets of reduced graphene oxide are peeled off, thereby making it easier to insert the nano-composite particles. The functional nano-composite particles provided by the present invention have good dispersibility and stability, and can be used in virus detection. DETAILED DESCRIPTION
[0022] The present invention will be further described below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0023] Example 1
[0024] 28g of ferric chloride hexahydrate and 13.8g of ferrous sulfate heptahydrate are added to 100ml of deionized water to prepare an iron salt solution, firstly the temperature is raised to 60°C at a rate of 5°C / min, 45ml of ammonia solution with a concentration of 20wt% is added dropwise at a rate of 1.15ml / min, after the addition is completed, stirring and reacting at 3000r / min for 20min, then the temperature is raised to 80°C at a rate of 10°C / min, aging treatment is performed for 20min, and finally cooled to room temperature, centrifuged, and the precipitate is washed with deionized water and anhydrous ethanol in turn until neutral, and dispersed in anhydrous ethanol after drying to prepare a nano-iron tetroxide microsphere dispersion with a concentration of 1g / L;
[0025] 0.04 mol of tetraethyl orthosilicate and 100 ml of anhydrous ethanol are mixed to obtain a tetraethyl orthosilicate solution, which is then mixed with 100 ml of a nano-iron oxide microsphere dispersion and subjected to ultrasonic treatment, followed by dripping 1.5 ml of a 5 wt % ammonia solution at a speed of 0.35 ml / L, stirring at 5000 r / min and room temperature for 1 hour, and finally dripping 6 ml of a 0.08 mol / L yttrium nitrate solution at a speed of 0.35 ml / min, stirring at 2000 r / min and room temperature for 4 hours, centrifuging the reaction solution after the reaction is completed, washing the precipitate obtained by centrifugation to neutrality, drying, and finally calcining at 400° C. for 2 hours to obtain nanocomposite particles;
[0026] 0.5 g of the above-prepared nanocomposite particles were dispersed in 100 ml of deionized water, and then 100 ml of an ethanol dispersion of reduced graphene oxide with a concentration of 0.1 g / L was added, and ultrasonic treatment was performed at room temperature and 300 W power for 1 h, and then filtered and the precipitate was dried to obtain functional nanocomposite particles.
[0027] Example 2
[0028] 28g of ferric chloride hexahydrate and 13.8g of ferrous sulfate heptahydrate are added to 100ml of deionized water to prepare an iron salt solution, firstly the temperature is raised to 70°C at a rate of 5°C / min, 45ml of a 20wt% ammonia solution is added dropwise at a rate of 1.35ml / min, after the addition is completed, the mixture is stirred at 5000r / min for 30min, then the temperature is raised to 85°C at a rate of 10°C / min, aged for 40min, finally cooled to room temperature, centrifuged, the precipitate is washed with deionized water and anhydrous ethanol in turn until neutral, dried and dispersed in anhydrous ethanol to prepare a nano-iron tetroxide microsphere dispersion with a concentration of 2g / L;
[0029] 0.04 mol of tetraethyl orthosilicate and 100 ml of anhydrous ethanol are mixed to obtain a tetraethyl orthosilicate solution, which is then mixed with 100 ml of a nano-iron oxide microsphere dispersion and subjected to ultrasonic treatment, followed by dripping 1.5 ml of a 10 wt% ammonia solution at a speed of 0.55 ml / L, stirring at 6000 r / min and room temperature for 2 hours, and finally dripping 6 ml of a 00.12 mol / L yttrium nitrate solution at a speed of 0.35 ml / min, stirring at 3000 r / min and room temperature for 6 hours, centrifuging the reaction solution after the reaction is completed, washing the precipitate obtained by centrifugation to neutrality, drying, and finally calcining at 400° C. for 3 hours to obtain nanocomposite particles;
[0030] 0.5 g of the above-prepared nanocomposite particles were dispersed in 100 ml of deionized water, and then 200 ml of an ethanol dispersion of reduced graphene oxide with a concentration of 0.2 g / L was added, and ultrasonic treatment was performed at room temperature and 500 W power for 3 h, and then filtered and the precipitate was dried to obtain functional nanocomposite particles.
[0031] Example 3
[0032] 28g of ferric chloride hexahydrate and 13.8g of ferrous sulfate heptahydrate are added to 100ml of deionized water to prepare an iron salt solution, firstly, the temperature is raised to 65°C at a rate of 5°C / min, 45ml of a 20wt% ammonia solution is added dropwise at a rate of 1.25ml / min, after the addition is completed, the mixture is stirred at 3500r / min for 20min, then the temperature is raised to 80°C at a rate of 10°C / min, aged for 30min, finally cooled to room temperature, centrifuged, the precipitate is washed with deionized water and anhydrous ethanol in turn until neutral, dried and dispersed in anhydrous ethanol to prepare a nano-iron tetroxide microsphere dispersion with a concentration of 1.5g / L;
[0033] 0.04 mol of tetraethyl orthosilicate and 100 ml of anhydrous ethanol are mixed to obtain a tetraethyl orthosilicate solution, which is then mixed with 100 ml of a nano-iron oxide microsphere dispersion and subjected to ultrasonic treatment, followed by dripping 1.5 ml of a 6 wt % ammonia solution at a speed of 0.45 ml / L, stirring at 5500 r / min and room temperature for 1 hour, and finally dripping 6 ml of a 0.09 mol / L yttrium nitrate solution at a speed of 0.35 ml / min, stirring at 2000 r / min and room temperature for 4 hours, centrifuging the reaction solution after the reaction is completed, washing the precipitate obtained by centrifugation to neutrality, drying, and finally calcining at 400° C. for 2 hours to obtain nanocomposite particles;
[0034] 0.5 g of the above-prepared nanocomposite particles were dispersed in 100 ml of deionized water, and then 150 ml of an ethanol dispersion of reduced graphene oxide with a concentration of 0.15 g / L was added, and ultrasonic treatment was performed at room temperature and a power of 400 W for 2 h, and then filtered and the precipitate was dried to obtain functional nanocomposite particles.
[0035] Example 4
[0036] 28g of ferric chloride hexahydrate and 13.8g of ferrous sulfate heptahydrate are added to 100ml of deionized water to prepare an iron salt solution, firstly the temperature is raised to 70°C at a rate of 5°C / min, 45ml of a 20wt% ammonia solution is added dropwise at a rate of 1.15ml / min, after the addition is completed, stirring and reacting at 4000r / min for 20min, then the temperature is raised to 80°C at a rate of 10°C / min, aging treatment is performed for 40min, and finally cooled to room temperature, centrifuged, and the precipitate is washed with deionized water and anhydrous ethanol in sequence until neutral, and dispersed in anhydrous ethanol after drying to prepare a nano-iron tetroxide microsphere dispersion with a concentration of 1.5g / L;
[0037] 0.04 mol of tetraethyl orthosilicate and 100 ml of anhydrous ethanol are mixed to obtain a tetraethyl orthosilicate solution, which is then mixed with 100 ml of a nano-iron oxide microsphere dispersion and subjected to ultrasonic treatment, followed by dripping 1.5 ml of a 5 wt% ammonia solution at a speed of 0.4 ml / L, stirring at 5000 r / min and room temperature for 2 hours, and finally dripping 6 ml of a 0.1 mol / L yttrium nitrate solution at a speed of 0.35 ml / min, stirring at 3000 r / min and room temperature for 5 hours, centrifuging the reaction solution after the reaction is completed, washing the precipitate obtained by centrifugation to neutrality, drying, and finally calcining at 400° C. for 2 hours to obtain nanocomposite particles;
[0038] 0.5 g of the above-prepared nanocomposite particles were dispersed in 100 ml of deionized water, and then 100 ml of an ethanol dispersion of reduced graphene oxide with a concentration of 0.15 g / L was added, and ultrasonic treatment was performed at room temperature and a power of 400 W for 2 h, and then filtered and the precipitate was dried to obtain functional nanocomposite particles.
[0039] Example 5
[0040] 28g of ferric chloride hexahydrate and 13.8g of ferrous sulfate heptahydrate are added to 100ml of deionized water to prepare an iron salt solution, firstly, the temperature is raised to 70°C at a rate of 5°C / min, 45ml of a 20wt% ammonia solution is added dropwise at a rate of 1.25ml / min, after the addition is completed, the mixture is stirred and reacted at 4500r / min for 30min, then the temperature is raised to 85°C at a rate of 10°C / min, aged for 30min, finally cooled to room temperature, centrifuged, the precipitate is washed with deionized water and anhydrous ethanol in turn until it is neutral, dried and dispersed in anhydrous ethanol, and a nano-iron tetroxide microsphere dispersion with a concentration of 2g / L is prepared;
[0041] 0.04 mol of tetraethyl orthosilicate and 100 ml of anhydrous ethanol are mixed to obtain a tetraethyl orthosilicate solution, which is then mixed with 100 ml of a nano-iron oxide microsphere dispersion and subjected to ultrasonic treatment, followed by dripping 1.5 ml of an 8 wt % ammonia solution at a rate of 0.55 ml / L, stirring at 6000 r / min and room temperature for 1 hour, and finally dripping 6 ml of a 0.1 mol / L yttrium nitrate solution at a rate of 0.35 ml / min, stirring at 2500 r / min and room temperature for 6 hours, centrifuging the reaction solution after the reaction is completed, washing the precipitate obtained by centrifugation to neutrality, drying, and finally calcining at 400° C. for 3 hours to obtain nanocomposite particles;
[0042] 0.5 g of the above-prepared nanocomposite particles were dispersed in 100 ml of deionized water, and then 200 ml of an ethanol dispersion of reduced graphene oxide with a concentration of 0.2 g / L was added, and ultrasonic treatment was performed at room temperature and 500 W power for 2 h, and then filtered and the precipitate was dried to obtain functional nanocomposite particles.
[0043] The average particle size of the functional nanocomposite particles prepared in the above examples is 30-40 nm, and the detection rate of the functional nanocomposite particles used for hepatitis B virus detection is as high as 100%.
[0044] In addition, it should be understood that after reading the contents of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A functional nanocomposite particle, characterized in that: The invention comprises a graphene oxide substrate and nanocomposite particles dispersed between the graphene oxide layers and on the surface; the nanocomposite particles comprise nano-iron tetroxide microspheres and a yttrium-doped nano-silicon oxide shell layer coated on the outer layer of the nano-iron tetroxide microspheres; The preparation method comprises the following steps: (1) adding an iron source to deionized water to prepare an iron salt solution, slowly dropping an ammonia solution after heating for the first time, vigorously stirring and reacting for a period of time after the dropping is completed, then heating for the second time, aging treatment, and finally cooling to room temperature, centrifuging, washing the precipitate with deionized water and anhydrous ethanol in turn until neutral, drying and dispersing in anhydrous ethanol to prepare a nano-iron oxide microsphere dispersion; (2) mixing tetraethyl orthosilicate and anhydrous ethanol to obtain a tetraethyl orthosilicate solution, then mixing the tetraethyl orthosilicate solution with a nano-iron oxide microsphere dispersion and ultrasonically treating the mixture, then dropping an ammonia solution to carry out a first stirring reaction, and finally dropping an yttrium nitrate solution to carry out a second stirring reaction. After the reaction is completed, centrifuging the reaction solution, washing the precipitate obtained by centrifugation to neutrality, drying it, and finally calcining it to obtain nanocomposite particles; the concentration of the ammonia solution is 5-10wt%, the dropping speed of the ammonia solution is 0.35-0.55ml / L, the concentration of the yttrium nitrate solution is 0.08-0.12mol / L, and the dropping speed of the yttrium nitrate solution is 0.35ml / min; the volume ratio of the ammonia solution, the yttrium nitrate solution, and the tetraethyl orthosilicate solution is 1:(3-5):(60-70); (3) The nanocomposite particles prepared above are dispersed in deionized water, and then an ethanol dispersion of reduced graphene oxide is added, and ultrasonic treatment is performed at room temperature and a power of 300-500 W for 1-3 hours, and then filtration is performed and the precipitate is dried to obtain functional nanocomposite particles; the concentration of the ethanol dispersion of reduced graphene oxide is 0.1-0.2 g / L, and the material ratio of the nanocomposite particles, deionized water, and the ethanol dispersion of reduced graphene oxide is 0.5 g: 100 ml: (100-200) ml.
2. The functional nanocomposite particle according to claim 1, characterized in that: In step (1), the iron source is a mixture of ferric chloride hexahydrate and ferrous sulfate heptahydrate, the molar ratio of the two is 2:1, the concentration of trivalent iron ions in the iron salt solution is 1-2 mol / L; the concentration of the ammonia solution is 20wt%, the dripping speed of the ammonia solution is 1.15-1.35ml / min, and the material ratio of ferric chloride hexahydrate to ammonia solution is 0.005mol:(2-3)ml.
3. The functional nanocomposite particle according to claim 1, characterized in that: In step (1), the heating rate during the first heating is 5°C / min, the stirring speed of the stirring reaction is 3000-5000r / min, the time is 20-30min, and the temperature is 60-70°C; the heating rate during the second heating is 10°C / min, the temperature of the aging treatment is 80-85°C, and the time is 20-40min.
4. The functional nanocomposite particle according to claim 1, characterized in that: In step (2), the concentration of the tetraethyl orthosilicate solution is 0.3-0.5 mol / L, the concentration of the nano-ferroferric oxide microsphere dispersion is 1-2 g / L, and the volume ratio of the tetraethyl orthosilicate solution to the nano-ferroferric oxide microsphere dispersion is 1:(1-2).
5. The functional nanocomposite particle according to claim 1, characterized in that: In step (2), the stirring speed of the first stirring reaction is 5000-6000 r / min, the reaction time is 1-2 h, and the reaction temperature is room temperature; the speed of the second stirring reaction is 2000-3000 r / min, the reaction time is 4-6 h, and the reaction temperature is room temperature.
6. The functional nanocomposite particle according to claim 1, characterized in that: In step (2), the calcination temperature is 400° C. and the calcination time is 2-3 hours.
7. Use of the functional nanocomposite particles according to any one of claims 2 to 6 in virus detection.
Citation Information
Patent Citations
Nanoparticles used for biological detection with fluoride lutecium as main component
CN102735659A
A method for preparing functionalized magnetic microspheres, the magnetic microspheres and their applications
CN112246196B